A survey of the current status of library automation in Malaysian Chinese secondary schools / Tee Lay Swee - Tee, Lay Swee (2004)
The study was undertaken to determine the current status of library automation in Malaysian Chinese secondary schools (MCSSs), which comprise the Independent Chinese Secondary School (ICSS) and the National-type Secondary School (Chinese) (NTSS [C]). This study employed a survey research method. It primarily used mailed questionnaire for data collection. Telephone interviews and personal interviews were carried out to gather supporting data. An 8-page questionnaire, divided into 12 parts, with 45 questions was mailed to the school libraries from all the 60 ICSS and 76 NTSS (C) throughout the country. A total of 89 respondents (65.4%) returned the questionnaires, of which 56 (73.7%) were from NTSS (C) and 33 (55.0%) from ICSS. The study showed that the MCSS libraries only start to adopt library automation during the 1990s and actively involved in library automation starting the year 2000. As at 31st March 2003, there are only 43.8% libraries (39.3% NTSS (C) and 51.5% ICSS) implementing library automation. A total of 50 (56.2%) libraries are not automated, however 39 of them (78.0%) plan to do in the future. The study found that circulation is the function mostly automated by libraries, followed by cataloguing. Turnkey system is the choice for most automated NTSS (C) libraries, whereas ICSS, opt for systems developed in-house. The research study has also identified important factors in determining the types of systems used, and areas need for future planning initiatives in implementing library automation.